Studi Komparasi Hasil Belajar Biologi dengan Pembelajaran INSTAD (Inquiry-STAD) dan Pembelajaran Inkuiri Terbimbing (Guided Inquiry) pada Siswa Kelas X SMA Negeri Gondangrejo Tahun Pelajaran 2012/2013 - Dina Dyah Saputri; Harlita Harlita; Puguh Karyanto (BIO-PEDAGOGI, 2013)
This research aimed to find out the effect of inquiry-STAD (InSTAD) learning compared with that of the guided inquiry on the biology learning achievement of the X graders of SMA Negeri Gondangrejo in the school year of 2012/2013.This study was a quasi-experiment research. The research design was Post-Test only with Nonequivalent Group using experiment 1 class (InSTAD strategy) and experiment 2 (guided inquiry strategy application). The population of research was all X graders of SMA Negeri Gondangrejo in the school year of 2012/2013. The sampling technique used was cluster sampling and two classes were taken as experiment 1 and experiment 2 classes. Techniques of collecting data used were multiple-choice test, observation sheet, and school document. The hypothesis testing was done using t-test. The conclusion of this research were have not differences result between InSTAD and Guided Inquiry learning toward student’s cognitive achievement in studying biology of  SMA Negeri Gondangrejo and  have  differences result between InSTAD and Guided Inquiry learning toward student’s afective and psycomotor achievement in studying biology of  SMA Negeri Gondangrejo. With this research is expected to have a discourse teachers and new knowledge and be able to apply this learning to improve science process skills in students so that the nature of biology can be realized students working scientifically. Key Words: INSTAD Learning , Guided Inquiry Learning, Biologi Learning Achievement